Colabotration Leaning of Scrambles with JIGSAW To Improve Student Activity and Mathematics Learning Outcomes - Laili Aprilia Widiawati; Fitriana Eka Chandra (Universitas Islam Jember, 2018)
The purpose of the research is to describe the students’ activities in using scramble with JIGSAW colaboration. And than to describe the mathematic students’ learning outcomes in using scramble with JIGSAW colaboration. The kind of the research is PTK with qualitative approach. The subjects of the research are students of class VII at MTs Miftahul Ulum. With the data collecting method that used in the research are questioner, documentation, observation, interview and test. The data analysis method that used is teacher activities analize, students’ activity analizes, and mathematic students learning outcomes analize. The results of the research there is increased activity and mathematic student learning outcomes.The percentasion of students’ activity in is 63 % become 96 % with verry good category. And for students learning outcomes is 78.30 with percentation is 70% become 85.15 with percentation is 90% Keyword: scramble jigsaw, mathetamtic learning outcomes